A dissolução da verdade do mundo em simulação e o retorno à vida: uma crítica ao niilismo de Baudrillard a partir de Michel Henry - Motta, Guilherme Carpes (2023)
The present dissertation is an analysis of what we conceive, from Baudrillard as postmodernity, the era of liquidation of all referentials and the loss of meaning, which the postmodern philosopher will call The Precession of Simulacra. We will follow Baudrillard in finding postmodernity as the era that crowns the death of meaning, in which all signs have become independent and without any connection with the real, not even the idea of the real subsist in this new system. However, contrary to what Baudrillard concludes, we are not willing to abandon the idea of meaning and adhere to nihilism of meaning, on the contrary, the research developed here already comes from a deep commitment, both epistemological and and existential: there is a meaning, it was just forgotten. With this, we will start from phenomenology to rediscover the forgotten meaning and oppose Baudrillard’s nihilism. Therefore, we should emphasize that the idea of the phenomenology defended here is anchored in the words: crisis, refusal and renewal, as Husserl defends in his essays organized under the title: “Europa: crise e renovação” (Europe: Crisis and Renewal). In this light, we understand that we are going through, as Husserl was, a moment of crisis of meaning, placing ourselves as phenomenologists in the position of refusing to abandon the idea of meaning and seeking, in phenomenology, therefore, in philosophy, the renewal of the idea of meaning. We believe that Husserl, despite his efforts and very useful finding to sustain meaning, is unable to fully embrace it, as he ends up, just like the others philosophies of his time and before him, by depositing meaning in the World, externally, in ekstase (ecstasy). For that reason, starting from the movement initiated by Husserl, we are going to Michel Henry in his philosophy and phenomenology of Life to seek, now without losing the fundamental original point, a critique of the idea of nihilism defended by Baudrillard and the hope of overcoming The Precession of Simulacra and rescue of meaning, no longer a simulated meaning as the Truth of the World, but a meaning deeply rooted in the most original and fundamental point: the pathetic reality of Life self-affecting itself and in itself, giving itself, therefore, as an absolute meaning.